Time-Varying Expected Small Firm Returns and Closed-End Fund Discounts - Swaminathan, Bhaskaran (Review of Financial Studies, 1996)
Journal Article Time-Varying Expected Small Firm Returns and Closed-End Fund Discounts Get access Bhaskaran Swaminathan Bhaskaran Swaminathan Cornell University Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 9, Issue 3, July 1996, Pages 845–887, https://doi.org/10.1093/rfs/9.3.845 Published: 03 June 2015